CONFLICT BETWEEN TRADEMARK AND GEOGRAPHICAL INDICATION. CASE OF PROTECTED DENOMINATION OF ORIGIN „SALAPARUTA” - Cristiana BUDILEANU (Challenges of the Knowledge Society)
Multiple signs are used in commerce for identifying traders and their products. These signs have usually their own system of protection, with their rules for registration and actions against they are protected. However, these signs often enter into conflicts. Depending on the signs entered into conflict, there are legal provisions which regulate the way in which these conflicts are solved. This is the case of conflicts between trademarks and geographical indications registered at EU level. Both these signs are part of intellectual property system, and their importance was proven over time both from consumer protection point of view, but also from business point of view. This paper is proposing to present a case referred to the CJEU for a preliminary ruling related to the conflict between multiple earlier trademarks used for wine products and a geographical indication registered at EU level also for wine products.